Peculiarities of stress relaxation of nanostructured alloy Zr1Nb after various influences - Sokolenko, V.I.; Karaseva, E.V.; Mats, A.V.; Savchuk, E.S.; Frolov, V.A. (Вопросы атомной науки и техники, 2017)
Processes of relaxation of internal stresses in the nanocrystalline alloy Zr1Nb after various thermomechanical influences was studied. The relationship of structural states obtained as a result of the relaxation effects with the laws of plastic deformation during creep were established. Shown that heat treatments of nanostructured alloy Zr1Nb, which provide the increase of the plasticity, changed qualitatively the alloy structure, destructing the nanostructured state, that results to decrease of the mechanical characteristics of the material and the degree of resistance to subsequent deformation during the creep at the temperature of 700 K. Ultrasonic processing reduces the level of internal stress of nanostructured material by forming the equilibrium structure of boundaries without noticeable growth of grains. During subsequent creep deformation at 700 K of nanostructured alloy Zr1Nb, subjected to ultrasonic treatment, the relaxation of the internal stresses due to dynamic recrystallization and the formation of new stable nanostructure take place that leads to the marked increase of the material thermomechanical stability.